2019
DOI: 10.1186/s13071-019-3681-7
|View full text |Cite
|
Sign up to set email alerts
|

Lineage-specific rapid diagnostic tests can resolve Trypanosoma cruzi TcII/V/VI ecological and epidemiological associations in the Argentine Chaco

Abstract: Background Trypanosoma cruzi, the protozoan agent of Chagas disease, is comprised of at least 6 genetic lineages (TcI-TcVI). Their geographical distribution, clinical associations and reservoir hosts are not fully elucidated, as genotyping is hampered due to the difficulty in isolating representative populations of organisms. Lineage-specific serological techniques may address these issues. Methods Trypanosoma cruzi lineage-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 54 publications
3
22
0
Order By: Relevance
“…Armadillos, especially D. novemcinctus, have been reported as natural hosts of TcIII throughout South America [11,40,41], thus the absence of TcII/V/VI infections from all 49 armadillos was not surprising. Although Chagas Sero K-SeT was shown to be able to detect infection in armadillo [20], positive test line intensity was weak; Protein A may be more appropriate than Protein G for binding of armadillo IgG, as others have reported [42], and which we observed here. No armadillo-specific conjugate was available for ELISA; this also encourages further deployment of Protein A for these important reservoirs hosts.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Armadillos, especially D. novemcinctus, have been reported as natural hosts of TcIII throughout South America [11,40,41], thus the absence of TcII/V/VI infections from all 49 armadillos was not surprising. Although Chagas Sero K-SeT was shown to be able to detect infection in armadillo [20], positive test line intensity was weak; Protein A may be more appropriate than Protein G for binding of armadillo IgG, as others have reported [42], and which we observed here. No armadillo-specific conjugate was available for ELISA; this also encourages further deployment of Protein A for these important reservoirs hosts.…”
Section: Discussionsupporting
confidence: 57%
“…Regarding the latter point, the application of serology based on lineage-specific antigens has great potential for resolving the cryptic ecological cycles and the discovery of novel reservoir hosts of this parasite. Applications of T. cruzi lineage-specific serology to naturally-infected animals are with dogs [17,26], primates [18] and sympatric dogs, cats, and armadillo [20]. We have applied Chagas Sero K-SeT to exploit the capacity of Protein G to recognise TSSApep-II/V/VI specific IgG from a range of mammalian Orders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Availability of gTSSA-I serology enables parallel investigation of clinical status associated with TcI infection, and serological detection of sporadic TcII/V/VI and TcI co-infections, which occur in some Bolivian and Brazilian endemic foci 40 , 41 . As with application of TSSA-II/V/VI serology to sylvatic mammals 20 , 21 , 23 , 42 , 43 , gTSSA-I can be deployed for resolution of TcI domestic and sylvatic transmission cycles, and for discovery of reservoir hosts. Thus, expression of L. tarentolae recombinant antigens representing epitopes specific to each of the T. cruzi lineages, may facilitate comprehensive epidemiological investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TcII/V/VI serology, adaptable to rapid diagnostic test (RDT) format, demonstrated that among Bolivian patients stratified by severity of cardiomyopathy, TcII/V/VI seropositives were five-fold more prevalent in the severe versus no evidence of cardiomyopathy groups 22 . RDTs also identified TcII/V/VI seropositive sympatric humans and dogs in the Argentine Chaco 23 .…”
mentioning
confidence: 90%